2012
DOI: 10.5603/fhc.2012.0074
|View full text |Cite
|
Sign up to set email alerts
|

Hsp-27 Expression in Invasive Ductal Breast Carcinoma

Abstract: Abstract:The aim of this study was to determine the intensity of Hsp27 protein expression in fibrocystic breast changes (FC) and invasive ductal breast carcinoma (IDC) and to examine its impact on patients' clinico-pathological characteristics and overall survival. Immunohistochemical reactions were conducted on archival samples of 20 cases of FC and 101 cases of IDC treated in 1999-2002. Nuclear-cytoplasmic Hsp27 expression was observed in 92 (92.1%) of the examined cases of IDC, and all the cases of FC. Sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…This correlation was further validated by direct in vitro overexpression of HSP27, which indicated that enforced HSP27 promoted the function and the self‐renewal markers of CSC in SACC. This finding is in agreement with several reports, which stated that in other cancers (breast, prostate and ovarian cancer), HSP27 was a marker that was applied to determine negative prognosis .…”
Section: Discussionsupporting
confidence: 93%
“…This correlation was further validated by direct in vitro overexpression of HSP27, which indicated that enforced HSP27 promoted the function and the self‐renewal markers of CSC in SACC. This finding is in agreement with several reports, which stated that in other cancers (breast, prostate and ovarian cancer), HSP27 was a marker that was applied to determine negative prognosis .…”
Section: Discussionsupporting
confidence: 93%
“…Hsps can be classified according to their molecular weight, for example, hsp27, hsp40, hsp60, hsp70, and hsp90. Altered hsp expression has been observed in breast, gastric, and colorectal cancers [Kanazawa et al, ; Partida‐Rodriguez et al, ; Grzegrzolka et al, ], and the knockdown of hsp has been shown to stop tumor migration [Bausero et al, ]. Hsp has also been reported to be a prognostic factor in patients with some tumors such as breast cancer [Thanner et al, ; Lee et al, ].…”
mentioning
confidence: 99%
“…Hsp60 and Hsp90 are present on the surface of tumor cells and are secreted by these cells via exosomes, which makes these two chaperones promising, easily accessible biomarkers [ 114 , 115 ]. Likewise, the chaperones Hsp10 and Hsp27 have also been implicated in multifunctional chaperone networks in invasive BC [ 116 ].…”
Section: Hsp27 Hsp60 Hsp70 and Hsp90 In Bc Therapeutics: Negative Cha...mentioning
confidence: 99%